2011
DOI: 10.4028/www.scientific.net/amr.356-360.2015
|View full text |Cite
|
Sign up to set email alerts
|

Study on Electrosorption Removal of Chloride Ion from Reclaimed Water

Abstract: The electrosorption technology for removal of chloride ion is researched by the static adsorption experiment, and various factors of the impact of the removal efficiency, combined with the removal of water quality and water treatment requirements, best adsorption conditions is identified that voltage is 5V, plate spacing is 1.0cm, adsorption time is 15min. Electrosorption technology in wastewater recycling project has certain benefits at economic, environmental and social, and have certain application value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…By contrast, alumina inorganic salts are easily controlled during gel preparation and are more economical. Many strategies, including ion-exchange resin, electrosorption ion removal and inorganic ion exchanger [28][29][30][31] for chloride ion removal, have been developed. Wu et al [32] fabricated Al 2 O 3 -SiO 2 composite aerogels via TEOS and AlCl 3 •6H 2 O as precursors, which showed a γ-Al 2 O 3 phase and high SSA of 630.6 m 2 /g after heat treatment at 600 • C. However, the SSA of Al 2 O 3 -SiO 2 composite aerogels decreased to 277.7 m 2 /g due to volume shrinkage after heat treatment at 1000 • C. Chen et al [33] prepared Al 2 O 3 -SiO 2 aerogels using TEOS and AlCl 3 •6H 2 O as precursors and found that the samples with a molar ratio of Al/Si = 3:1 possessed better thermal insulation performance and thermal stability, but the alumina proportion was ultra-high, which was not suitable for industrial-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, alumina inorganic salts are easily controlled during gel preparation and are more economical. Many strategies, including ion-exchange resin, electrosorption ion removal and inorganic ion exchanger [28][29][30][31] for chloride ion removal, have been developed. Wu et al [32] fabricated Al 2 O 3 -SiO 2 composite aerogels via TEOS and AlCl 3 •6H 2 O as precursors, which showed a γ-Al 2 O 3 phase and high SSA of 630.6 m 2 /g after heat treatment at 600 • C. However, the SSA of Al 2 O 3 -SiO 2 composite aerogels decreased to 277.7 m 2 /g due to volume shrinkage after heat treatment at 1000 • C. Chen et al [33] prepared Al 2 O 3 -SiO 2 aerogels using TEOS and AlCl 3 •6H 2 O as precursors and found that the samples with a molar ratio of Al/Si = 3:1 possessed better thermal insulation performance and thermal stability, but the alumina proportion was ultra-high, which was not suitable for industrial-scale production.…”
Section: Introductionmentioning
confidence: 99%